Management of Pseudomyxoma Peritonei Syndrome during Pregnancy - Aditanzil, Hanny (Indonesian Socety of Obstetrics and Gynecology, 2013)
Objectives: To improve skill in making a diagnosis and management of pseudomyxoma peritoneum originating borderline mucinous ovarian tumor during pregnancy. Methods: Case report. Conclusion: Diagnosis of pseudomyxoma peritoneum during pregnancy is difficult before surgery. Management is based on grade of malignancy and gestational age of pregnancy. [Indones J Obstet Gynecol 2013; 1-3: 161-5] Keywords: mucinous tumor, pregnancy, pseudomyxoma peritoneum